PENGARUH TINGKAT BUNGA (Interest Rate) TERHADAP PERTUMBUHAN PENJUALAN (Net Sales Growth) MOTOR MERK YAMAHA VIXION PADA CV THAMRIN BROTHERS CABANG CURUP - Paddery; Feri; Inez Ramadani (Politeknik Raflesia Press, 2022)
The purpose of this study was to determine the effect of interest rate on sales growth (Net Sales Growth) of Yamaha Vixion Brand Motorcycle at CV Thamrin Brothers, Curup Branch. The analysis used in this study was quantitative analysis method and qualitative analysis. The estimation in regression analysis shows that there is a negative influence between the Interest Rate on Sales Growth (Net Sales Growth) for Yamaha Vixion Brand Motorcycles at CV Thamrin Brothers, Curup Branch, meaning that if the interest rate increases it will be followed by a decrease in sales volume growth. The results of hypothesis testing indicate that there is a significant influence between the Interest Rate on Net Sales Growth for Yamaha Vixion Brand Motorcycles at CV Thamrin Brothers, Curup Branch, this is indicated by the t-count value which is greater than t-table and the hypothesis research is acceptable.